Competencias del orientador de centros subvencionados vulnerables para la mejora de la convivencia escolar: Competencies of the counselor of subsidized vulnerability centers for the improvement of school life - Daniel Villarroel Montaner, Joaquín Gairín Sallàn, José Garcés Bustamante (Revista de Orientación Educacional, 2019)
Este estudio levanta un perfil de competencias del orientador escolar en centros educativos subvencionados en contextos vulnerables, en base a las interrogantes: ¿Hay un perfil de competencias para el orientador del subsistema particular subvencionado chileno vulnerable? Cuando un representante legal contrata a este profesional, ¿con qué tipo de perfil se guía? Se trata de una investigación cualitativa con una metodología de datos mixta mediante un diseño etnográfico, analizándose 3 documentos oficiales, 1 focus group con registro multimedia, 3 cuestionarios y 5 reuniones del Comité de Orientación Escolar, contando con la participación de directivos, orientadores y expertos. Los resultados arrojaron cuatro dominios de intervención: Liderazgo orientador, Gestión de proyectos de orientación, Orientación vocacional y el desarrollo personal y Acompañamiento pedagógico con dieciséis competencias profesionales. Abstract: This study is about creating a skill profile of the school counselor of vulnerable subsidized schools, according to the following questions: Is there a skill profile for the school counselor of vulnerable schools of the subsidized subsystem in Chile? When a legal representative hires this profesional, what type of profile is based on? It is an investigation based on a qualitative study using a mixed methodology and ethnographic design, analyzing 3 official documents and 1 focus group with multimedia records, 3 questionnaires and 5 meetings of four Committee on School Counselor, with the participation of school managers, school counselors and experts in the field. The results of the research produced four domains: counselor leadership, guidance management projects, vocational guidance and personal development and pedagogical accompaniment with sixteen professional skills.